Ill-fated fortune - Chow, Jennifer J. (Chow, Jennifer J. Magical fortune cookie novel., 2024)
"Felicity Jin grew up literally hanging onto Mom's apron strings in their magical bakery in the quaint town of Pixie, California. Her mother's enchanted baked goods, including puffy pineapple buns and creamy egg tarts, bring instant joy to all who consume them. Felicity has always been hesitant in the kitchen herself after many failed attempts, but a takeout meal gone wrong inspires her to craft some handmade fortune cookies. They become so popular that Felicity runs out of generic fortunes and starts making her own personalized predictions. When one customer's ill-fated fortune results in his murder, Felicity's suspiciously specific fortune has the police focusing on her as the main culprit. Now Felicity must find a way to turn her luck around and get cleared from suspicion."--